Identification of Interface Structure for a Topological CoS2Single Crystal in Oxygen Evolution Reaction with High Intrinsic Reactivity - Kang, Yu; He, Yangkun; Pohl, Darius; Rellinghaus, Bernd; Chen, Dong; Schmidt, Marcus; Suess, Vicky; Mu, Qingge; Li, Fan; Yang, Qun; Chen, Hedong; Ma, Yufei; et al. (ACS Applied Materials and Interfaces, 2022)
Transition metal chalcogenides such as CoS2have been reported as competitive catalysts for oxygen evolution reaction. It has been well confirmed that surface modification is inevitable in such a process, with the formation of different re-constructed oxide layers. However, which oxide species should be responsible for the optimized catalytic efficiencies and the detailed interface structure between the modified layer and precatalyst remain controversial. Here, a topological CoS2single crystal with a well-defined exposed surface is used as a model catalyst, which makes the direct investigation of the interface structure possible. Cross-sectional transmission electron microscopy of the sample reveals the formation of a 2 nm thickness Co3O4layer that grows epitaxially on the CoS2surface. Thick CoO pieces are also observed and are loosely attached to the bulk crystal. The compact Co3O4interface structure can result in the fast electron transfer from adsorbed O species to the bulk crystal compared with CoO pieces as evidenced by the electrochemical impedance measurements. This leads to the competitive apparent and intrinsic reactivity of the crystal despite the low surface geometric area. These findings are helpful for the understanding of catalytic origins of transition metal chalcogenides and the designing of high-performance catalysts with interface-phase engineering.
CRIS-Team Scopus Importer:2023-03-20
Keywords: cobalt disulfide; cobalt oxide; interface structure; oxygen evolution reaction; topological metal